Resenhas - Vargas, Thiago; Lourenço, Ciro (Discurso, 2022)
Resenhas de Paul Sagar. Adam Smith Reconsidered. History, Liberty, and the Foundations of Modern Politics. Princeton University Press, 2022, por Thiago Vargas (USP-FAPESP) e de Antoine Lilti. L’héritage des Lumières. Ambivalences de la modernité. Seuil ; Gallimard, 2019, por Ciro Lourenço (USP-Paris 1)